2019
DOI: 10.1590/1981-22562019022.190053
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic accidents involving elderly people: an integrative review

Abstract: Objective: To identify the epidemiological and socio-demographic profile of elderly victims of traffic accidents reported in articles published in scientific literature from 2013 to 2018. Method: The Literatura Latino Americana em Ciências da Saúde (Latin American Literature in Health Sciences), Base de Dados de Enfermagem (Database in Nursing), Scientific Electronic Library Online, and Medical Literature Analysis and Retrieval System Online databases were used, with the guiding question being: What is the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The demographic characteristics of the present study demonstrated that the highest frequency of call-outs involved older adults, aged 60 to 69 years old. A recent review study on traffic accidents involving such older adults identified, as a demographic profile, the male sex and the age group from 60 to 69 years 14 . The fact that younger older adults are the most affected shows is most likely because such adults have a more active life, with independence and autonomy, and activities outside the home form part of their daily routine 15 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The demographic characteristics of the present study demonstrated that the highest frequency of call-outs involved older adults, aged 60 to 69 years old. A recent review study on traffic accidents involving such older adults identified, as a demographic profile, the male sex and the age group from 60 to 69 years 14 . The fact that younger older adults are the most affected shows is most likely because such adults have a more active life, with independence and autonomy, and activities outside the home form part of their daily routine 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, the spatial-temporal analysis of accidents involving older adults found that they occur on weekdays, during the day and in the coldest months of the year 13 . In a review of accidents involving older adults 14 , it was observed that such adults use selfregulatory behaviors, that is, those involving the self-reported decision to protect oneself, with the adoption of strategies such as reducing exposure to traffic, driving at a reduced speed and avoiding driving at night.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations